Oral lesions as Risk Factors of Systemic Diseases - Cuadrao Zavaleta, Luis Cuadrao Zavaleta (2014)
Oral health problems influence the general condition of people. The clinical diagnosis of oral disease can give an idea of the etiology and prognosis, but this not directly reflects the level of disturbance. For some people oral diseases indicate a risk factor but are not for life, not severe enough to disable their abilities, but their consequences can impact daily life at different degrees and cause disability altering the perception of psychosocial development. Several authors mention oral signs as risk factor for systemic diseases. Pathologies of root canal considered as a place of outbreak of systemic actinomycosis. Chronic ulceration of the hard palate where the sign of undiagnosed pulmonary tuberculosis is presented is also described; likewise secondary syphilis is initially diagnosed by oral lesions. Other authors argue that primary Ewing sarcoma of bone surrounds the head and neck before impact systemically. It is also described the presence of cytomegalovirus in oral mucosal as one of the first manifestations of AIDS. Hematogenous exposure to oral streptococci has been recognized as potential initiator factor of bacterial endocarditis. The infection has been recognized as a risk factor for atherogenesis and thrombotic events. Significant association between periodontal component of the dental index and cerebrovascular ischemia were found. There are oral lesions that are risk factors for developing systemic disease. Renal osteodystrophy and changes in the bone tissue are a consequence of renal failure. Changes in alveolar bone associated with renal osteodystrophy are similar to those found in primary hyperparathyroidism and include generalized loss of bone density, thinning of the cortical bone and partial or total loss of the lamina dura.